STUNTING AND OBESITY PREVENTION EDUCATION AT PARENTS OF PAUD STUDENTS ON THE COMMEMORATIONOF NATIONAL NUTRITION DAY: EDUKASI PENCEGAHAN STUNTING DAN OBESITAS PADA ORANGTUA SISWA PAUD PADA PERINGATAN HARI GIZI NASIONAL - Ratih Damayanti; Anita Dewi Moelyaningrum; Inar Garmarini (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Indonesia is experiencing a double burden of nutrition because at this time there are still malnutrition problems, one of which is stunting and also over nutrition problems, namely obesity in children. Objective: The purpose of this community service activity is to increase the knowledge of parents/guardians of TK/KB Lasiyam Surabaya students about